Exploring Sustainable Pathways for Citizen Science Projects in China's Watershed Governance: The Case Study of Guiyang. - Huang, Xuan; Xu, Junqing (Environmental Management, 2025)
Citizen science (CS) is increasingly recognized as a valuable tool in global environmental governance. In China, however, CS projects often face challenges, such as low public engagement, limited institutional support, and weak long-term sustainability. This study investigates Guiyang's CS initiatives in watershed governance through an action research approach, applying two analytical frameworks, a six-stage lifecycle model and a participation typology, to examine project design, implementation, and the evolution of citizen involvement. Findings show that Guiyang's CS projects, although rooted in rural communities, expanded the coverage and responsiveness of environmental monitoring by mobilizing local knowledge and activating dense community networks. A "point-to-surface" strategy, using trained civilian environmental supervisors to engage local residents, was supported by expert assistance and structured training to overcome technical and knowledge barriers. The study reveals that, by responding to environmental governance needs, embedding CS within rural social structures, and fostering adaptive capacities, these projects integrated into China's policy-driven governance model and local socio-cultural contexts. Three key drivers of sustained development were identified: responsive governance mechanisms, digital tools and a supportive policy environment. Nonetheless, persistent challenges remain, including unstable participation, uneven technical capacity, and intermittent policy support. This study illustrates how CS can be effectively localized in different governance systems and highlights new pathways for participatory environmental governance in the Global South.